2019
DOI: 10.3390/molecules24091831
|View full text |Cite
|
Sign up to set email alerts
|

A NMR-Based Metabonomics Approach to Determine Protective Effect of a Combination of Multiple Components Derived from Naodesheng on Ischemic Stroke Rats

Abstract: Naodesheng (NDS) is a widely used traditional Chinese medicine (TCM) prescription for the treatment of ischemic stroke. A combination of 10 components is derived from NDS. They are: Notoginsenoside R1, ginsenoside Rg1, ginsenoside b1, ginsenoside Rd, hydroxysafflor yellow A, senkyunolide I, puerarin, daidzein, vitexin, and ferulic acid. This study aimed to investigate the protective effect of the ten-component combination derived from NDS (TCNDS) on ischemic stroke rats with a middle cerebral artery occlusion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 32 publications
1
8
0
Order By: Relevance
“…In addition, Nelson et al ( 68 ) used LC/MS to determine 144 metabolites from 367 acute stroke patients, compared cardiac and non-cardiogenic samples, and they found that the tricarboxylic acid metabolite α-ketoglutarate and malate were associated with cardiogenic stroke, which is encouragingly consistent with our findings. Meanwhile, other metabolites we found have also been widely reported by researchers, for example, the changing content of uridine ( 69 ), 3-hydroxybutyric acid ( 70 ), L-cysteine ( 71 ), and asymmetric dimethylarginine ( 72 ).…”
Section: Discussionsupporting
confidence: 67%
“…In addition, Nelson et al ( 68 ) used LC/MS to determine 144 metabolites from 367 acute stroke patients, compared cardiac and non-cardiogenic samples, and they found that the tricarboxylic acid metabolite α-ketoglutarate and malate were associated with cardiogenic stroke, which is encouragingly consistent with our findings. Meanwhile, other metabolites we found have also been widely reported by researchers, for example, the changing content of uridine ( 69 ), 3-hydroxybutyric acid ( 70 ), L-cysteine ( 71 ), and asymmetric dimethylarginine ( 72 ).…”
Section: Discussionsupporting
confidence: 67%
“…Modern scholars of TCM also point out that blood stasis is the principal problem in the process of occurrence, development, and outcome of ischemic stroke (Wang et al, 2014;Zhong et al, 2015;Sun et al, 2016;Chai and Zhang, 2018). Therefore, in the prevention (Chang et al, 2016;Tsai et al, 2016;Song et al, 2019), treatment (Chen et al, 2019;Hsu et al, 2019;Luo et al, 2019), and rehabilitation (Huang et al, 2018;Zhao et al, 2018) of ischemic stroke, conventional treatment combined with drugs that promote blood circulation and remove blood stasis can be an effective intervention.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, NDS also exhibits significant antioxidative activity, as showed by a decrease of LDH and MDA production, increase of SOD generation in plasma, and enhancement of brain levels of leucine, isoleucine, choline, and myo-inositol. 96 NG-R1 is also the main bioactive and circulating compound of XueShuanTong, which has been predicted to show high potentials for drug interactions mediated by organic anion-transporting polypeptide (OATP)1B. 97 Conventional pharmacotherapy has been implicated in the treatment of complex diseases, and the use of herbal medicinal products or botanical dietary supplements is prevalent in China.…”
Section: Clinical Perspectivesmentioning
confidence: 99%